Irradiation-induced degradation of PTB7 investigated by valence band and S 2p photoelectron spectroscopy. (1st July 2016) - Darlatt, Erik; Muhsin, Burhan; Roesch, Roland; Lupulescu, Cosmin; Roth, Friedrich; Kolbe, Michael; Gottwald, Alexander; Hoppe, Harald; Richter, Mathias
Abstract: Monochromatic radiation with known absolute radiant power from an undulator at the electron storage ring Metrology Light Source (MLS) was used to irradiate PTB7 (a thieno[3, 4-b]thiophene-alt-benzodithiophene polymer) thin films at wavelengths (photon energies) of 185 nm (6.70 eV), 220 nm (5.64 eV), 300 nm (4.13 eV), 320 nm (3.88 eV), 356 nm (3.48 eV) and 675 nm (1.84 eV) under ultra-high vacuum conditions for the investigation of radiation-induced degradation effects. The characterization of the thin films is focused at ultraviolet photoelectron spectroscopy (UPS) of valence bands and is complemented by S 2 p x-ray photoelectron spectroscopy (S 2 p XPS) before and after the irradiation procedure. The radiant exposure was determined for each irradiation by means of photodiodes traceably calibrated to the international system of units SI. The valence band spectra show the strongest changes for the shortest wavelengths and no degradation effect at 356 nm and 675 nm even with the highest radiant exposure applied. In the spectral range where the Sun appears bright on the Earth's surface, no degradation effects are observed.